Russia in the system of functioning models of the modern world market for arms and military equipment - D. A. Repnikov (Вестник университета)
In   the context of   modern geopolitical conflicts, which have led to  complications in   the international trade and investment cooperation between countries, there are serious changes in  the positions of   states in  the global export of  arms and military equipment (hereinafter referred to   as AME). Structural transformations in   the international exchange of  the AME are also conditioned by   the clash of   economic interests of   individual countries due to   globalisation of  recent decades as   well as   by the use of   various models of  production and export of  the AME at   the national level. As  shown in   our article, states of   the world are seriously differentiated in   their own production of   the AME according to  the degree of   their dependence on   imports and foreign suppliers of   components and technologies. The fact that countries can be   advanced participants in   the technological chain or   be niche suppliers determines new directions for their international specialisation and, largely, the rules and nature of   competition in   the modern AME market. As   part of   the presented analysis of   the national specialisation models of  states, the competitive advantages and weaknesses of   Russia as   one of   the leading arms exporters in   the world are shown. At   the same time, the foreign policy and economic risks of  strengthening its position in  the global AME trade have been assessed. Based on   the results of   the study, directions for reinforcing the potential of  the Russian military-industrial complex in   the world AME market have been formulated.